Lactobacillus paragasseri HM018, Isolated from Human Milk, Improves Intestinal Metabolism in Germ-Free Mice Humanized with Gut Microbiota from Pregnant Women during Pregnancy - TIAN Xiaoyan, ZHAO Junying, LIU Yanpin, LIU Bin, ZHANG Zhenzhen, ZHAO Yujin, ZHAO Yanyan, YUAN Yuying, LIU Lu, WANG Yaru, QIAO Weicang, CHEN Lijun (Shipin Kexue)
In this study, we investigated the effect of Lactobacillus paragasseri HM018 on the intestinal microbiota and metabolism in humanized pregnant mice with fecal microbiota transplantation. Eight-week-old germ-free mice were transplanted with fecal bacterial suspensions from healthy pregnant women to develop a germ-free humanized mouse model. After conception, the mice were treated by L. paragasseri HM018 for three weeks. The results showed that the Shannon and Simpson indexes of gut microbiota in the treatment group were higher significantly than those of the model group after 14 days. The abundance of Roseburia and Clostridium and the content of bile acids, especially secondary bile acids, in feces increased significantly in the treatment group compared with the model group. In addition, 37 serum metabolites involved in 20 metabolic pathways changed significantly, among which pyridoxine and myristoleic acid were up-regulated and pelargonic acid was down-regulated. In addition, L. paragasseri HM018 had significant effects on the glucagon signaling pathway and showed a tendency to increase short-chain fatty acids and tryptophan. This study shows that L. paragasseri HM018 improves gut microbiota and bile acid metabolism, thus having potential health benefits.